Portable pressure chamber for manual camera-assisted monitoring of leaf water potential - Willian Viana Campos; José Teixeira Filho; Alcebiades Rebouças São José (HardwareX)
This paper presents a detailed description of the assembly and components of a pressure chamber used to measure leaf water potential in leaves, particularly in african mahogany. The assembly and components of this pressure chamber were specifically designed for field experiments. The image capture camera plays a crucial role in recording changes occurring in the sample during measurements. It can also be coupled with image analysis devices to quantify alterations in leaf cells and stomata under varying pressure levels. A cylindrical acrylic support ensures the stability of the camera during the procedure, providing additional protection. The pressure chamber assembly is designed to securely accommodate leaves during measurements, facilitating the manipulation of gas levels and enabling the creation of a controlled atmosphere within the chamber. The sealing valve is an essential component, allowing precise control of internal pressure, preventing leaks, and enabling the study of plant responses under different atmospheric conditions. This pressure chamber proven to be a valuable tool in plant ecophysiology, enabling precise monitoring of plant responses to diverse environmental conditions. Consequently, it contributes significantly to the conservation and sustainable management of african mahogany and other plant species in their natural environments.